Millennial‐Scale Changes in Bottom Water Temperature and Water Mass Exchange Through the Fram Strait 79°N, 63‐13 ka. Issue 2 (17th February 2021) - El bani Altuna, N.; Ezat, M. M.; Greaves, M.; Rasmussen, T. L.
Abstract: The Svalbard margin, in the eastern Fram Strait with its high sediment accumulation, form a key area for the reconstruction of water mass and heat exchange between the North Atlantic and Arctic Ocean in relation to abrupt climate changes as seen in glacial Greenland Interstadial and Greenland Stadial (GI‐GS) events. Here, we present a bottom water temperature (BWT) record from the northern Nordic Seas (79°N) at 1, 273 m water depth based on benthic foraminiferal Mg/Ca. The BWT reconstructions, combined with benthic foraminiferal stable isotopes, benthic foraminiferal fauna compositions and ice‐rafted debris (IRD), reveal at least two distinctive scenarios for the GI‐GS events during the last glacial period (13–63 ka). During GIs, conditions were similar to modern with high productivity, low BWT and deep convection. During GS6, GS8, and GS15 and during Heinrich Stadials (HSs), BWT increased up to 5°C ± 1°C generally concomitant with low planktic and benthic δ 18 O. Our results suggest, that during some GSs and HSs, deep water generation was reduced, allowing the subsurface Atlantic water (AW) to thicken and deepen down to at least the core site depth. A strong halocline during HSs and GSs prevented heat release from the subsurface AW, which we can now trace from 45°N in the North Atlantic to the Arctic Ocean >79°N. Surfacing of the salty Atlantic subsurface water preconditioned the Nordic seas for convection. Release of the subsurface heat from this vast reservoir must have contributed to the large and abrupt atmospheric warmings at the start of GIs. Plain Language Summary: The Fram Strait is an area where warm and salty Atlantic water (AW) enters the Arctic Ocean from the North Atlantic Ocean. As it flows northwards in the Nordic Seas, the AW mass releases heat to the atmosphere and sinks to form deep cold water, both moderating regional climate and driving deep ocean circulation. To better understand future changes in ocean circulation and interactions under ongoing climate change, it is necessary to study past oceanic changes in relation to climate change. We investigated benthic foraminifera (single‐celled organisms with shells living at the sea floor) with the aim of reconstructing bottom water temperature variations during the last ice age during abrupt atmospheric warmings and coolings on millennial time scales. Our results show that during events of extremely low atmospheric temperature, the deep ocean from the northern North Atlantic to the Arctic Ocean was warmer than today. The ocean surface was cold and stratified due to the presence of polar meltwater. The accumulation of subsurface heat in this vast area toward the end of these periods and decrease of meltwater supply probably broke the stratification, and the subsequent heat release from the ocean to the atmosphere contributed to the abrupt atmospheric warming and onset of renewed convection and cold deep water formation. Key Points: Bottom water temperature in the Fram Strait increased up to 5°C during Heinrich Stadials (HSs) due to subsurface flow of Atlantic water During HSs, a strong halocline prevented heat loss from the Atlantic water, from 45°N in the North Atlantic to the Arctic Ocean >79°N Release of subsurface heat from this vast area contributed to the abrupt regional atmospheric warmings at the start of Greenland Interstadials